Genetic surfing in human populations: from genes to genomes. (December 2016) - Peischl, Stephan; Dupanloup, Isabelle; Bosshard, Lars; Excoffier, Laurent
Abstract : Genetic surfing describes the spatial spread and increase in frequency of variants that are not lost by genetic drift and serial migrant sampling during a range expansion. Genetic surfing does not modify the total number of derived alleles in a population or in an individual genome, but it leads to a loss of heterozygosity along the expansion axis, implying that derived alleles are more often in homozygous state. Genetic surfing also affects selected variants on the wave front, making them behave almost like neutral variants during the expansion. In agreement with theoretical predictions, human genomic data reveals an increase in recessive mutation load with distance from Africa, an expansion load likely to have developed during the expansions of human populations out of Africa.